Electrical power monitoring system for solar power plants based on the Internet of Things - Hartoyo Hartoyo; Sa'adilah Rosyadi; Usman Nursusanto (Center for Science and Technology, IAIN Surakarta, 2024)
The objectives of this research are: first, to develop an electrical power monitoring system for solar power plants based on the Internet of Things; second, to evaluate the performance of this tool; and third, to assess the contribution of this tool to support the achievement of the SDGs. The development method involves three stages: analysis, design, and development. The development process was carried out at the off grid solar power lant house in Magelang, Indonesia. The measuring instruments used for testing included a multimeter and an ammeter. Testing adhered to International Electrotechnical (IEC) standards. The analysis technique employed was quantitative descriptive analysis, involving the calculation of averages and percentages. The results are as follows. First, the Internet of Things-based electrical power monitoring system for solar power plants consists of several components, including the PZEM 004T sensor, NodeMCU Wi-fi module, adapter, and I2C Liquid Crystal Display (LCD). This system is capable of monitoring current, voltage and electrical power in real time, both locally and remotely. Second, the test results demonstrate that this tool performs well, with an average deviation of less than 5%. Specifically, the deviations for voltage, current, and power measurements are 0.49%, 2.15%, and 1.09%, respectively. Third, this tool provides significant value by enhancing the performance and sustainability of solar energy systems, thereby contributing significantly to global efforts in achieving Sustainable Development Goals.